THE INFLUENCE OF MATHEMATICAL RESILIENCE AND NUMERACY SKILLS ON STUDENTS' MATHEMATICAL PROBLEM-SOLVING ABILITIES - Ummu 'Athiyah Sudirman; Ja’faruddin Ja’faruddin; Hamda Hamda (JURNAL NALAR PENDIDIKAN, 2025)
This ex post facto study examines the influence of mathematical resilience and numeracy skills on the mathematical problem-solving abilities of eighth-grade students in Sungguminasa. A sample of 100 students was selected from a population of 1,436 using a proportional random sampling method. Data were collected through numeracy tests, problem-solving tests, and resilience questionnaires, then analyzed using descriptive statistics and multiple regression. The results show that both variables have a significant positive effect, both simultaneously and individually, with coefficients of 0.087 and 0.595, respectively. These findings emphasize the importance of strengthening numeracy and resilience in mathematics education.